Prevalence of osteoporosis, associated fractures, and level of knowledge about this problem among the patients undergoing medical rehabilitation - L. A. Marchenkova; E. V. Makarova; M. Yu. Gerasimenko (Лечащий Врач, 2021)
The questionnaire survey studied the prevalence of osteoporosis and low-traumatic fractures and the level of knowledge about osteoporosis in 600 men and women aged 50 years and older undergoing inpatient rehabilitation treatment. Low level of knowledge about osteoporosis and insufficient frequency of prescription of antiosteoporotic therapy among patients with the previously defined diagnosis were revealed, which indicates the need for widespread use of educational programs as part of comprehensive medical rehabilitation to prevent new osteoporotic fractures.